Diseño conceptual de un robot prototipo limpiador de ventanas de vidrio en rascacielos con Solidworks y Simulink. (2022)
At present, the cleaning of glass for buildings is carried out by different employees, analyzing this problem it is observed that there is a lack of immersion of technology in these works. This text presents a conceptual prototype of a window cleaning robot, capable of taking on this task without compromising human life. In this document you will find the analysis and study of the robot prototype and the tools that were used for its design and analysis, based mostly on study thanks to research carried out by other entities in search of reducing this problem. In order to reach the design presented in the document, an investigation was carried out on various platforms and documents carried out by students in late careers on the same subject, where some only analyzed certain structures and others made a design. Analyzing these designs in which the same filmmakers give an opinion on the shortcomings of the same, in this work the possible improvements for the design are proposed, reaching the obtaining of an optimal design, less invasive to the eye and with a significant improvement over time. of the cleaning process with respect to the time taken by the human personnel for the windows of the skyscrapers. At the end of the design, a significant improvement is obtained in the traditional cleaning time (with human personnel), a visually minimally invasive design and with a higher safety standard than previous and existing designs.